Origem e evolução do IFSULDEMINAS Campus Inconfidentes: qual o princípio pedagógico - Bresci, Melissa Salaro (2017)
The Federal Institute of Education, Science and Technology of the South of Minas Gerais, Inconfidentes campus (IFSULDEMINAS – campus Inconfidentes) is one of the institutions that composed since 2008 the Federal Network of Education. The Inconfidentes campus is the result of a series of transformations in the field of professional education, having started its activities in 1918 as Patronato Agrícola Visconde de Mauá, since then has developed professional technical training. The present research aims to understand the origin and evolution of the campus Inconfidentes (education institution), as a way of knowing the steps undertaken until the constitution as a campus of the Federal Institute, from there to identify how the training of students in secondary education integrated. This research sought to delineate its evolutionary process until 2016, based on documents referring to its origin and institutional evolution, such as decrees, laws, educational guidelines for professional education, theoretical reference on professional education in Brazil, especially on secondary education integrated, Seeking the current debate for the Federal Institutes. We also used as source for this research data obtained through research data obtained through quantitative and qualitative research carried out with teachers, administrative technicians and students through questionnaires in order to know the reality of the debates about training and perspectives for the high school professional education level. The results showed that vocational training at the Inconfidentes campus is still very much linked to a utilitarian perspective and too far away from what is recommended for integrated secondary education. In the general context, it can be observed that the education offered by the Inconfidentes campus is still linked to training for the labor market and that the search for secondary education integrated is not necessarily due to professionalization.